Fiqh Learning Using Media and Its Implication towards Students Understanding: A Case Study at MAN 2 Mataram - Syukri Syukri (UIN Mataram, 2022)
The fiqh (Islamic law) learning process using media among Islamic studies teachers at MAN 2 Mataram has huge implications for the quality of the learning process. Fiqh learning, especially on the topics of hajj and umrah as well as the treatment of the deceased, with media support, turns out to be exciting, and it accelerates and enhances students' understanding. Teachers of Islamic studies can explain hajj and umrah as well as bathing and praying the deceased through a demonstration using a miniature of Ka’bah and a doll representing a corpse, respectively. Students practice the lessons individually and in groups upon the teacher's demonstration. The process of Fiqh learning using media has an implication towards the increase of students understanding and their ability to memorize the lessons. Keywords: Fiqh learning, media, method, demonstration, practice Abstrak: Proses pembelajaran Fikh menggunakan alat peraga di kalangan guru agama Islam Madrasah Aliyah Negeri (MAN) 2 Mataram memberikan implikasi yang besar terhadap peningkatan pemahaman siswa cukup tinggi dan memiliki kemampuan daya ingat yang lama. Pembelajaran mata pelajaran Fikh menggunakan alat peraga khusus pada materi haji dan umrah menggunakan kabah dan cara memandikan mayat dan menshalatkannyn menggunakan boneka sangat menyenangkan, mempercepat, dan memperjelas pemahaman siswa. Metode diterapkan guru agama Islam adalah metode demonstratif dengan alat peraga miniatur kabah dan boneka mayat. Usai guru mendemonstrasikan alat peraga sesuai materi, siswa langsung mempraktekkan secara individu dan kelompok. Pembelajaran Fikh menggunakan alat peraga menghasilkan peningkatkan pemahaman siswa yang cukup signifikans dan memiliki kemampuan daya ingat yang sangat lama.